(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
This paper examines the moral didactic framework of the sacred Valley of Cypresses, as described in Cervantes’ sixth book, La Galatea. A scrupulous analysis of the form, style and content of this episode reveals the hermeneutic significance of one of the most inspiring episodes of pastoral literature.